Beyond Textual Prohibition : Maslahah Social Control and the Customary Ban on Intracommunity Marriage in West Sumatra - Tiara Anisa; Dedi Sumanto; Tasnim Rahman Fitra; Zainab Yusuf (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2025)
The interaction between Islamic law and customary law remains a significant issue in contemporary Islamic family law, particularly in communities where local traditions continue to regulate marital practices beyond the explicit provisions of Islamic jurisprudence. One such tradition is the prohibition of same-village marriage in Korong Toboh Mandahiling, Nagari Balah Aia, West Sumatra. While Islamic law does not prohibit marriage between individuals from the same village, the custom has been maintained across generations as a binding social norm. Existing studies have primarily focused on normative tensions between Islamic law and adat, with limited attention given to the sociological rationality and maqasid al-shariah dimensions underlying such prohibitions. This study aims to examine the sociological foundations of the same-village marriage prohibition and evaluate its relevance through the perspectives of legal pluralism, 'urf, and maqasid al-shariah. Employing a qualitative socio-legal approach, data were collected through interviews with customary leaders, religious figures, community elders, and local residents, supported by observation and document analysis. The findings reveal that the prohibition functions as a mechanism for preventing communal conflict, expanding inter-village kinship networks, and preserving social harmony. From the perspective of Islamic law, the custom may be classified as 'urf sahih because it does not contradict Shariah principles and serves recognized social benefits. Furthermore, the prohibition contributes to the realization of several maqasid dimensions, namely the protection of lineage (hifz al-nasl), social dignity (hifz al-'ird), and public welfare (maslahah 'ammah). This study argues that the prohibition represents a contextual manifestation of living Islamic law in which customary norms and Islamic legal principles operate as complementary rather than competing systems. The article contributes to contemporary debates on legal pluralism and the contextual realization of Islamic legal objectives within Muslim societies.